Determination of an experimental geoid at Deception Island, South Shetland Islands, Antarctica. Issue 4 (24th February 2016) - Jigena, Bismarck; Berrocoso, Manuel; Torrecillas, Cristina; Vidal, Juan; Barbero, Ignacio; Fernandez-Ros, Alberto
Abstract: Deception Island is an active volcano located in Bransfield Strait. Its volcanic activity is linked to the presence of gravity anomalies that influence the definition of the geoid. In this paper, a precise undulation geoid model (GeoiDEC14) has been computed from GPS, gravimetric and levelling measurements. GeoiDEC14 highlights local anomalies of the island that match with hot spots, such as the minimum values shown in Fumarole Bay and Whalers Bay (fumarole areas), or the maximum values found in the remains of lava at Colatinas, Black Glacier and Murature Point. Comparison of GeoiDEC14 with global models always shows negative values due to an average of 18.80 m for our model compared to 19.80–20.60 m for models such as ITSG-Grace2014s, EGM08, AIUG-Grace03s or EGM96. This difference is due to the lack of resolution of global models and to the volcanic activity on the island. To confirm the results, the same measurements were taken on nearby Livingston Island. The values of geoid undulation on this island reaffirm the lack of detail in the global geoid in the area, presenting an average of 18.90 m, similar to the average value of GeoiDEC14.